Implementasi Aplikasi Inventory Management berbasis Google AppSheet untuk Pengendalian Persediaan: Studi Kasus pada PLN UP3 Surakarta - Lira Anjani; Aris Eddy Sarwono (LPPM Universitas Sains dan Teknologi Komputer, 2026)
The rapid development of information technology requires organizations to manage inventory data more efficiently and accurately in order to support operational activities and decision making. PLN UP3 Surakarta still performs manual reconciliation between inventory data in the Systems, Applications, and Products in Data Processing (SAP) system and physical stock in the warehouse. This condition may cause information delays, data inconsistencies, and increased workload for warehouse staff. Therefore, a supporting system is needed to present inventory data in a simpler and more accessible form. This study aims to implement a Google AppSheet-based inventory control application as a supporting system for inventory control at PLN UP3 Surakarta. The research method used is the System Development Life Cycle (SDLC), which consists of planning, requirements analysis, system design, implementation, and testing. The application utilizes Google Spreadsheet as a database to store and manage inventory data, which is then displayed through a simple and mobile-accessible interface. The results indicate that the developed application is able to accelerate data searching, improve the accuracy of reconciliation between SAP data and physical inventory, and support more effective inventory monitoring and control. In addition, the application facilitates warehouse staff in accessing inventory information anytime and anywhere. Therefore, the implementation of a Google AppSheet-based inventory control application can improve the efficiency and effectiveness of inventory management.